Rare, rarer, lung involvement in adult-onset Still's disease: A mini-review - Nies, Jasper F.; Schneider, Udo; Krusche, Martin (Frontiers in Medicine, 2022)
Adult-onset Still’s disease (AOSD) is a polygenic systemic autoinflammatory disease which is associated with increased morbidity and mortality. Pulmonary involvement is a rare, but serious complication of AOSD. As in AOSD, IL-1b, IL-18, and IL-6 dominate the molecular pathogenesis, which mediate a type 1 and type 3 inflammatory signature of the adaptive immune system. This is evidenced by the success of IL-1- and IL-6 inhibition in the management of AOSD. However, anaphylactic reactions to treatment with IL-1- or IL-6-inhibitors is currently being discussed as a potential trigger for lung involvement inf AOSD, while genetic risk factors have also been identified. Clinically, pulmonary involvement in AOSD can manifest in many different forms. Parenchymal inflammation with peripheral consolidations is the most frequent form while PAH is less common, but often very difficult to manage. This mini-review provides an overview of the pathophysiology as well as the clinical presentation and the diagnostic features of pulmonary involvement in AOSD.